Incidence and risk factors of emergence agitation in pediatric patients after general anesthesia - Ananchanok Saringcarinkul (2018)
Objective: To study the incidence and evaluate factors associated with emergence agitation (EA) in pediatrics after general anesthesia. Material and Method: A prospective observational study was conducted in 250 pediatric patients aged 2-9 years, who received general anesthesia for various operative procedures in Maharaj Nakorn Chiang Mai Hospital between October 2006 and September 2007. The incidence of EA was assessed. Difficult parental-separation behavior, pharmacologic and non-pharmacologic interventions, and adverse events were also recorded. Univariate and multivariate analysis were used to determine the factors associated with EA. A p-value of less than 0.05 was considered significant. Results: One hundred and eight children (43.2%) had EA, with an average duration of 9.6 ± 6.8 minutes. EA associated with adverse events occurred in 32 agitated children (29.6%). From univariate analysis, factors associated with EA were difficult parental-separation behavior, preschool age (2-5 years), and general anesthesia with sevoflurane. However, difficult parental-separation behavior, and preschool age were the only factors significantly associated with EA in the multiple logistic regression analysis with OR = 3.021 (95% CI = 1.680, 5.431, p < 0.001) and OR = 1.857(95% CI = 1.075, 3.206, p = 0.026), respectively. Conclusion: The present study indicated that the incidence of EA was high in PACU. Preschool children and difficult parental-separation behavior were the predictive factors of agitation on emergence. Therefore, anesthesia personnel responsible for pediatric anesthesia should have essential skills and knowledge to effectively care for children before, during, and after an operation, including implementing the methods that minimize incidence of EA.